2020
DOI: 10.1101/2020.10.03.324806
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Universal Stress Protein upregulated by hypoxia may contribute to chronic lung colonisation and intramacrophage survival in cystic fibrosis

Abstract: SummaryUniversal stress proteins (USPs) are ubiquitously expressed in bacteria, plants and eukaryotes and play a lead role in adaptation to environmental conditions. In Gram negative bacteria they enable adaption of bacterial pathogens to the conditions encountered in the human niche, including hypoxia, oxidative stress, osmotic stress, nutrient deficiency or acid stress, thereby facilitating colonisation. We previously reported that all six USP proteins encoded within a low-oxygen responsive locus in Burkhold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…Burkholderia cepacia complex (Bcc) is an opportunistic pathogen not only present among CF patients but also in immunocompromised individuals, pharmaceutical plants, products and disinfectants, whose eradication becomes difficult to undertake once colonization has been established [ 54 ]. B. cenocepacia , one of the B. cepacia strains, is considered more virulent than P. aeruginosa because it is associated with a terminal illness known as “cepacia syndrome” that is typified by high temperatures, septicemia, confluent bronchopneumonia and a general decline in pulmonary function, which leads to patient death within days of infection in comparison to the months after which P. aeruginosa patients eventually succumb to it [ 55 , 56 ].…”
Section: Usps In Cystic Fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“…Burkholderia cepacia complex (Bcc) is an opportunistic pathogen not only present among CF patients but also in immunocompromised individuals, pharmaceutical plants, products and disinfectants, whose eradication becomes difficult to undertake once colonization has been established [ 54 ]. B. cenocepacia , one of the B. cepacia strains, is considered more virulent than P. aeruginosa because it is associated with a terminal illness known as “cepacia syndrome” that is typified by high temperatures, septicemia, confluent bronchopneumonia and a general decline in pulmonary function, which leads to patient death within days of infection in comparison to the months after which P. aeruginosa patients eventually succumb to it [ 55 , 56 ].…”
Section: Usps In Cystic Fibrosismentioning
confidence: 99%
“…All the proteins exhibited an increase (of up to 40-fold) in production during chronic lung infection. Subsequent studies then showed that Usp76 and Usp92 displayed different functions showcasing the functional variety of these proteins [ 54 ]. Usp76 was, however, highlighted as the most significant contributor to B. cenocepacia survival owing to the changes in phenotype observed in Δusp76 mutants in comparison to the wild type and its role in protecting against oxidative stress and attachment to host cells in comparison to Usp92.…”
Section: Usps In Cystic Fibrosismentioning
confidence: 99%
“…Universal stress proteins (USPs) were first discovered in 1990 [ 1 , 2 ]. They are typical stress-inducible proteins that are essential in various cellular responses under biotic or abiotic stress conditions such as nutrient deficiency [ 3 ], heat or cold stimulation [ 4 ], oxidative stress [ 5 ], and osmotic stress [ 4 ].…”
Section: Introductionmentioning
confidence: 99%